2009
DOI: 10.1093/hmg/ddp465
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of superovulation: loss of maternal and paternal imprinted methylation in a dose-dependent manner

Abstract: Superovulation or ovarian stimulation is currently an indispensable assisted reproductive technology (ART) for human subfertility/infertility treatment. Recently, increased frequencies of imprinting disorders have been correlated with ARTs. Significantly, for Angelman and Beckwith-Wiedemann Syndromes, patients have been identified where ovarian stimulation was the only procedure used by the couple undergoing ART. In many cases, increased risk of genomic imprinting disorders has been attributed to superovulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
231
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(255 citation statements)
references
References 57 publications
17
231
3
4
Order By: Relevance
“…Our results showed losses of methylation on the normally hypermethylated allele of imprinted genes but not gain of methylation on the normally hypomethylated allele in ART-generated offspring. These results are consistent with a study by Market-Velker et al (17) that analyzed offspring from mice subjected to ovarian stimulation, but contrast with the pattern of aberrant hypermethylation observed by Turan et al (18) in human tissues from offspring generated by ART.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed losses of methylation on the normally hypermethylated allele of imprinted genes but not gain of methylation on the normally hypomethylated allele in ART-generated offspring. These results are consistent with a study by Market-Velker et al (17) that analyzed offspring from mice subjected to ovarian stimulation, but contrast with the pattern of aberrant hypermethylation observed by Turan et al (18) in human tissues from offspring generated by ART.…”
Section: Discussionsupporting
confidence: 92%
“…B6(CAST7) mice possess a chromosome 7 from the Mus musculus castaneus (Cast) strain on a C57BL/6 (B6) background. B6(CAST7) females were crossed with DBA males and the ensuing F1 progeny carried several previously characterized strain-specific polymorphisms that were used to distinguish the parental alleles of imprinted genes on chromosome 7 (17,23,24). Because of the significant labor involved in generating mice by ICSI and analyzing allelespecific DNA methylation and expression patterns, our study was limited to examining six mice (three male, three female) conceived through natural reproduction and six mice (three male, three female) created through the use of ICSI.…”
Section: Methodsmentioning
confidence: 99%
“…Other reports suggest that proper acquisition of methylation can be perturbed by superovulation; loss of methylation was detected in oocytes at several maternally methylated ICRs (human MEST, mouse Peg3, Snrpn and Kcnq1ot1 ICRs) and gain of methylation was detected at a paternally methylated ICR (human and mouse H19 ICRs) (Table 1). 89,90 A number of studies report that BWS and AS cases are overrepresented in children born through ART. 42,[91][92][93][94][95] However, other studies did not find evidence for increased risk for these diseases, 96,97 and the relationship between ART and imprinting disorders remains to be established.…”
Section: Molar Pregnancy Infertility Assisted Reproductive Technolomentioning
confidence: 99%
“…Such a gain of maternal methylation and a loss of paternal methylation at H19DMR have been recently documented in mouse blastocysts and were attributed to superovulation induced imprinting disorders. 17 The authors did not give information on the imprint in the oocytes themselves. On the other hand, we found almost no residual methylation on the maternal allele of control human blastocysts while Market-Velker et al 17 showed an average methylation of the maternal allele of H19 of up to 15% in mouse blastocysts obtained from spontaneously ovulated female, demonstrating one more time the discrepancies existing between species at the level of epigenome regulation.…”
mentioning
confidence: 99%